Techno-economic Classification of Contradictions and Related Strategies of Solution. (2015) - Cascini, Gaetano; Fiorineschi, Lorenzo; Frillici, Francesco Saverio; Rissone, Paolo
Abstract: One of the most important objectives of modern product development is the fulfillment of the requirements derived from stakeholder/customer needs. For this reason, modern design processes start from an accurate definition of those final product features able to satisfy a given set of customer needs. However, it is well acknowledged that, during a common design process, it is often possible to find requirements conflicting with each other. Thus the choice of a successful design strategy is critical. The aim of this work is to investigate the possibility to find a rule suitable to indicate the best side of the contradiction to process in order to solve technical problems, also usable by engineers with limited experience with TRIZ. The analysis has been formerly operated on well-known solved problems belonging to Classical TRIZ literature; the emerging evidences have been further checked on a set of case studies from the authors' industrial experience.